Ownership changes in the Hungarian healthcare sector, 1990-2017 - Mihalyi, Peter (Journal of Public Governance, 2018)
The paper’s objective is to provide a historical account of the most important changes in two aspects of Hungarian healthcare: financing and provision. It will be shown that after a promising start to the necessary post-communist reforms, a complete reversal took place after 2010. The separation between financing and provision ended. By 2017, the Ministry of the Economy – like the Planning Office under the socialist system – has regained absolute control over the entire healthcare sector, including both financing and provision. Even the Ministry of Health ceased to exist in 2010.